Accelerating climate adaptation in the Zambezi River Basin through digital innovations - Matchaya, Greenwell C.; Mukuyu, Patience; Rajapakse, Nilu (International Water Management Institute, 2023)
The Zambezi River Basin (ZRB) in southern Africa connects eight riparian countries—Angola, Botswana, Malawi, Mozambique, Namibia, Tanzania, Zambia, and Zimbabwe. The population there mostly reside rurally, and over 80 percent of agriculture is attributed to smallholder farmers facing the brunt of the climate crisis. Digital technologies can facilitate and enhance climate adaptation and resilience, but their potential in ZRB is unassessed and the use relatively low. Under the Integrated Development and Adaptation to Climate Change (PIDACC) program for the Zambezi, the African Development Bank (AfDB), in partnership with the Global Center on Adaptation (GCA), the International Water Management Institute (IWMI) and partners — Centre for Agriculture and Food Policy (CAFP), Zimbabwe and Indaba Agricultural Policy Research Institute (IAPRI), Zambia, undertook feasibility studies to mainstream climate-smart digital agricultural technologies into climate adaptation programs within the ZRB. The CGIAR initiative on Digital Innovation will build on the outcomes of this work to enhance digital inclusivity by providing a digital technologies solutions and services suite which is accessible, useful, desirable, and also socially inclusive.